1998
DOI: 10.1177/109861119800100303
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Considerations in Community Policing and Problem Solving

Abstract: Although the literature concerning community-oriented policing and problem solving (COPPS) is rapidly growing, very little has been written concerning its relationship with ethics—a relationship that is critical to the success of COPPS. Many academics and practitioners are concerned that the potential for ethical dilemmas is increased with the shift to COPPS, given the nature of ethics training, decentralization, expanded discretionary authority and officers' greater proximity to citizens. This article d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…Many studies have suggested that implementation of COP requires fundamental changes in organizational structures and others have argued that COP implementation would bring changes in organizational structure (Adams et al, 2002;Carter and Radelet, 1999;Eitle et al, 2005;Greene et al, 1994;Peak and Glensor, 1996). Typical aspects of organizational structures discussed in the prior studies can be categorized into one of the following: functional, occupational, spatial and vertical differentiation, as well as centralization, formalization, and administrative intensity (Langworthy, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have suggested that implementation of COP requires fundamental changes in organizational structures and others have argued that COP implementation would bring changes in organizational structure (Adams et al, 2002;Carter and Radelet, 1999;Eitle et al, 2005;Greene et al, 1994;Peak and Glensor, 1996). Typical aspects of organizational structures discussed in the prior studies can be categorized into one of the following: functional, occupational, spatial and vertical differentiation, as well as centralization, formalization, and administrative intensity (Langworthy, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…More generally, the recent emphasis on community policing indicates the need and relevance of the 'female' style to policing. Notwithstanding equalopportunity arguments to support the employment of women, Peak and Glensor (1996) asserted: 'As contemporary policing becomes more COPPS [communityoriented policing and problem-solving] oriented, the growing presence of women may help to improve its tarnished image; improve community relations; and foster a more flexible, less violent, approach to keeping the peace' (p. 162). Arguably, police services could benefit from examining more closely the ways in which skilled policewomen perform their duties and then educating male police officers in these techniques.…”
Section: Discussionmentioning
confidence: 98%
“…In a sense, that initial change movement can be partly interpreted as a form of internal emancipation and institutional loosening-up. One of the key concepts which began to emerge at that time was community-oriented policing or 'COP' (Peak & Glensor, 1996). It had its roots in a wish to fundamentally transform that traditional, rigid, overtly centralized, machine bureaucracy into a flexible institution.…”
Section: Structural and Cultural Changementioning
confidence: 99%